Corporate sustainability as a strategy : Case study of Aquaplastic in Russia - Krynina, Vlada (2018)
This thesis studies the complexity and multidimensional character of the sustainability management of an enterprise using a case of a medium – sized regional producer of pipes in Russia. The author has researched the variety of theoretical works on sustainability in both world and Russian academic publishing and attempted to apply the key ideas on the case of manufacturing company.